REFORMING BUSINESS ENGLISH TEACHING PRACTICES: PERCEPTIONS, CONSTRICTIONS, AND SOLUTIONS - Sabbah, Lyna (PEOPLE: International Journal of Social Sciences, 2019)
This research work is entitled “Reforming Business English Teaching Practices: Perceptions, Constrictions, and Solutions”. It is an attempt to explore the scarcities and the constraints confronted by the teachers of Business English in the Faculty of Economic Sciences, Management, and Commerce, at the University of Bejaia (Algeria) since Business English is one of the major branches of ESP courses. Accordingly, this investigation concerns itself with the issue of what challenges do this particular subset of Business English teachers meet and which remedial solutions can be suggested. To tackle this problem, we have put forward the hypothesis which states that “the whole amalgam of teaching policies, curricula, and strategies need to be revised in order to overcome the current existing limitations”. In order to collect data and check the correctness of our hypothesis, we have opted to the quantitative and the qualitative methods by means of a questionnaire designed for the teachers of Business English in the three departments at the level of the faculty along with an interview designed for the faculty’s chief leaders. The anticipated outcome of this project is to demonstrate the lack and the deficits in the contemporary process of Business English teaching at the University of Béjaia, then suggesting solutions for better future practices. This research work highlights the importance of rethinking and revising the existing policies starting from the ministry to the faculty level, focusing on collaboration between all the concerned parties. Besides, it points up redesigning and reshuffling the BE course curriculum according to learners’ needs by taking into account all the skills within the communicative competence. Therefore, this investigation can be a valuable contribution to the professional development of Business English teachers, hence, their learners’ feedback.